2021
DOI: 10.23970/ahrqepccer248
|View full text |Cite
|
Sign up to set email alerts
|

Prehabilitation and Rehabilitation for Major Joint Replacement

Abstract: Objectives. This systematic review evaluates the rehabilitation interventions for patients who have undergone (or will undergo) total knee arthroplasty (TKA) or total hip arthroplasty (THA) for the treatment of osteoarthritis. We addressed four Key Questions (KQs): comparisons of (1) rehabilitation prior (“prehabilitation”) to TKA versus no prehabilitation, (2) comparative effectiveness of different rehabilitation programs after TKA, (3) prehabilitation prior to THA versus no prehabilitation, (4) comparative e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 72 publications
(430 reference statements)
0
21
0
Order By: Relevance
“…Several previous studies and summary reports have examined the effectiveness of prehabilitation among patients with hip and knee replacements [ 26 , 27 , 28 ]. However, the results are ambiguous, a fact possibly explained by differences in the types of interventions used during prehabilitation and the lengths of the prehabilitation periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies and summary reports have examined the effectiveness of prehabilitation among patients with hip and knee replacements [ 26 , 27 , 28 ]. However, the results are ambiguous, a fact possibly explained by differences in the types of interventions used during prehabilitation and the lengths of the prehabilitation periods.…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of our prehabilitation program was demonstrated by the fact that three of our patients who underwent hip replacement surgery did not need postoperative rehabilitation in hospital at all due to their favorable functional condition. Butler et al and Konnyu et al demonstrated that THA patients who undergo prehabilitation require a shorter rehabilitation, as they reach adequate functionality and can leave the hospital earlier [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a systematic review (SR) 12 under the Agency for Healthcare Research and Quality (AHRQ) Evidence-based Practice Center Program to understand the effectiveness and comparative effectiveness of prehabilitation and rehabilitation for TKA and total hip arthroplasty (THA; see questions for the full review in Appendix A, Supplemental Digital Content 1, http://links.lww.com/PHM/B644). In this article, we address the effects and harms of rehabilitation for patients who underwent TKA on patient-reported outcomes, performance-based outcomes, and healthcare utilization after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the COVID‐19 epidemic introduced new peri‐TKR practice patterns that EHR notes are not prepared to evaluate. The incomplete data in today's RWD cannot generate best practice for content and dosage of PT interventions and changes in care patterns post TKR ( 6 , 7 ).…”
mentioning
confidence: 99%
“…Recently, this PT intervention taxonomy was applied to an Agency for Healthcare Research and Quality–funded systematic review of pre‐ and post–total knee and hip rehabilitation practices ( 7 ). Application of this detailed taxonomy demonstrates that, as in clinical practice, there is the significant heterogeneity of rehabilitation interventions reported in the literature (Table 1 ).…”
mentioning
confidence: 99%